2019
DOI: 10.1016/j.socscimed.2018.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Turning over a new leaf: The health-enabling capacities of nature contact in prison

Abstract: In this paper we explore the potential applicability of evidence of health-enabling effects of elements of the built environment - particularly access to nature - deriving from research in healthcare facilities to evidence-based design in the custodial context. Drawing on comparative qualitative research conducted in the UK and the Nordic region, we argue that although available data lack direct comparability, there is evidence that access to nature generates the same health-enabling effects in custody as are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 33 publications
2
39
0
1
Order By: Relevance
“…Mirroring those in previous studies (Nadkarni et al 2017, Moran andTurner, 2018), respondents frequently reported that both types of nature contact helped reduce stress and increased feelings of calm. They described them as relaxing, and supportive of a sense of peace and wellbeing; 'It makes a big difference to how I feel.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Mirroring those in previous studies (Nadkarni et al 2017, Moran andTurner, 2018), respondents frequently reported that both types of nature contact helped reduce stress and increased feelings of calm. They described them as relaxing, and supportive of a sense of peace and wellbeing; 'It makes a big difference to how I feel.…”
Section: Resultsmentioning
confidence: 64%
“…Despite the apposite nature of ART (noted by Söderlund and Newman 2017), this analytical framing has not been widely deployed in prisons, and relevant published studies of the potentially therapeutic effects of nature contact are scarce. Moore's 1981 paper reported fewer sickness calls made by prisoners with a view of nature from their cell, but since then knowledge about the impact of nature contact in prison had advanced relatively little until two recent and significant contributions by Nadkarni et al (2017) and Moran and Turner (2018). In framing their experimental study of the impact of viewing nature videos on solitary-confined prisoners in a US facility, Nadkarni et al (2017) differentiate between direct, indirect, and vicarious nature contact.…”
Section: Prison Environments and Artmentioning
confidence: 99%
See 2 more Smart Citations
“…McGeachan notes, however, that such changes in penal policy are difficult to enact and that after years of institutionalisation the agents within such spaces may be troubled by the intervention of caring moments which in this context are described as: “specialist support in a relatively unstructured and non‐punitive environment” (Bottomley et al., , p. 11). Given recent interest in contemporary cycles of therapeutic spaces in prison (Moran & Turner, ), it seems pertinent to reflect on historical geographies of such attempts. Notably, McGeachan observes that despite the introduction of such practices, the prison remains a harsh, punitive environment.…”
Section: Towards Geographies Of Troubling Institutionsmentioning
confidence: 99%